Stabilities of free and complexed human immunodeficiency virus p24 antigens during short- and long-term storage. - Arens, M (1997)
By the standard p24 assay there was a 25 to 27% decrease in free p24 antigen in serum after storage at 4 degrees C over 14 days but no loss at -70 degrees C. There was no loss at either temperature by the immune complex dissociation (ICD) procedure. Furthermore, there was no significant loss of detectable p24 in serum by either the ICD or the standard p24 assay after 700 days of storage at -70 degrees C.